Penerapan Model Pembelajaran Course Review Horay (CRH) pada Pembelajaran IPAS Siswa Kelas IV SDN 3 Megang Sakti - Muhamad Seto Satriyo; Doni Pestalozi; Yetty Trisnayanti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The low student learning outcomes in IPAS (Natural and Social Sciences) indicate a need to implement an engaging learning model that can boost student participation in the learning process. One such model is Course Review Horay (CRH), as it is capable of creating an enjoyable learning atmosphere. This study aims to determine the significant improvement in the learning outcomes of fourth-grade students of SDN 3 Megang Sakti in science after the implementation of the Course Review Horay (CRH) learning model. The research method used is a pre-experimental design with one group pre-test and post-test categories. The population in this study were all fourth-grade students of SDN 3 Megang Sakti, totaling 20 students and the research sample was fourth-grade students totaling 20 students, consisting of 8 male students and 12 female students taken by saturated sampling. The data collection technique used a multiple-choice test technique. The data analysis technique used a paired t-test. Based on the data analysis, the average pre-test score was 50.35 and the average post-test score was 82.30, with a t-count of -17.175 with df = 19 and a significance value (Sig. 2-tailed) of 0.05 (0.001 <0.05), so Ho was rejected and Ha was accepted. Thus, it can be concluded that the results of the science learning of fourth grade students at SDN 3 Megang Sakti after implementing the Course Review Horay (CRH) learning model can significantly improve student learning outcomes.